PENGARUH PENGUASAAN KONSEP BANGUN DATAR TERHADAP KEMAMPUAN SISWA MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR (Studi Kasus pada Siswa Kelas IX MTs Darul Ulum Waru Sidoarjo Tahun Ajaran 2016/2017) - Hartati, Sulis Janu; Sagala, Viktor; Heriyansah, Heriyansah (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
Students should know as that the importance of konsep. If the students gets a problem in solving mathematical problems related to the concept of the problem can be solved easily if the concept is understood in advance. For that, if students find problems which will be described in the discussion later that students will solve the problems about the geometry and the plane side as prerequisites must understand the concept of matter flat first. Of the above problems, as educator need to better understand character of the student, lest there favorite toward them. It will make the student themselves tend to be lazy and no curiosity about the material that is being taught. Thus, educator must work harder to make the students better. Keywords: plane concepts, capabilities geometry plane side